Optimized peptide functionalization of thiol‐acrylate emulsion‐templated porous polymers leads to expansion of human pluripotent stem cells in 3D culture. Issue 18 (9th March 2019) - Ratcliffe, Jessie L.; Walker, Marc; Eissa, Ahmed M.; Du, Shengrong; Przyborski, Stefan A.; Laslett, Andrew L.; Cameron, Neil R.
ABSTRACT: Highly porous polymers produced by polymerization of the continuous phase of a high internal phase emulsion have been developed as scaffolds for 3D culture of human pluripotent stem cells. These emulsion‐templated polymerized high internal phase emulsion (polyHIPE) materials have an interconnected network of pores that provide support for the cells, while also allowing both cell ingress and nutrient diffusion. Thiol‐acrylate polyHIPE materials were prepared by photopolymerization, which, due to a competing acrylate homopolymerization process, leads to a material with residual surface thiols. These thiols were then used as a handle to allow postpolymerization functionalization with both maleimide and a maleimide‐derivatized cyclo‐RGDfK peptide, via Michael addition under benign conditions. Functionalization was evaluated using an Ellman's colorimetric assay, to monitor the residual thiol concentration, and X‐ray photoelectron spectroscopy. Maleimide was used as a model molecule to optimize conditions prior to peptide‐functionalization. The use of triethylamine as a catalyst and a mixed ethanol‐aqueous solvent system led to optimized reaction between surface‐bound thiols and maleimide. Peptide‐functionalized materials showed improved attachment and infiltration of human pluripotent stem cells over 7 days, demonstrating their promise as a scaffold for 3D stem cell culture and expansion. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 1974–1981 Abstract : Optimised maleimide functionalization of thiol‐ene porous polymer scaffolds leads to efficient attachment of a cyclic RGD motif and enhanced 3D cell culture of human pluripotent stem cells.